Post-COVID-19 Vaccination and Long COVID: Insights from Patient-Reported Data - Tom C. Quach; Mitchell G. Miglis; Lu Tian; Hector Bonilla; Phillip C. Yang; Lauren Grossman; Amogha Paleru; Vincent Xin; Anushri Tiwari; Robert W. Shafer; Linda N. Geng (Vaccines)
Introduction: COVID-19 vaccinations reduce the severity and number of symptoms for acute SARS-CoV-2 infections and may reduce the risk of developing Long COVID, also known as post-acute sequelae of SARS-CoV-2 (PASC). Limited and heterogenous data exist on how these vaccinations received after COVID-19 infection might impact the symptoms and trajectory of PASC, once persistent symptoms have developed. Methods: We investigated the association of post-COVID-19 vaccination with any SARS-CoV-2 vaccine(s) on PASC symptoms in two independent cohorts: a retrospective chart review of self-reported data from patients (n = 128) with PASC seen in the Stanford PASC Clinic between May 2021 and May 2022 and a 2023 multinational survey assessment of individuals with PASC (n = 484). Findings: Within the PASC Clinic patient cohort (n = 128), 58.6% (n = 75) were female, and 41.4% (n = 53) were male; 50% (n = 64) were white, and 38.3% (n = 49) were non-white. A total of 60.2% (n = 77) of PASC Clinic patients reported no change in their PASC symptoms after vaccination, 17.2% (n = 22) reported improved symptoms, and 22.7% (n = 29) reported worsened symptoms. In the multinational survey cohort (n = 484), 380 were from the U.S., and 104 were from outside the U.S.; 88.4% (n = 428) were female, and 11.6% (n = 56) were male; and 88.8% (n = 430) were white, and 11.2% (n = 54) were non-white. The distribution of survey self-reported vaccine effects on PASC symptoms was 20.2% worsened (n = 98), 60.5% no effect (n = 293), and 19.2% improved (n = 93). In both cohorts, demographic features, including age, sex, and race/ethnicity, were not significantly associated with post-vaccination PASC symptom changes. There was also a non-significant difference in the median dates of COVID-19 infection among the different outcomes. BMI was significant for symptom improvement (p = 0.026) in the PASC Clinic cohort, while a history of booster doses was significant for symptom improvement (p < 0.001) in the survey cohort. Conclusions: Most individuals with PASC did not report significant changes in their overall PASC symptoms following COVID-19 vaccinations received after PASC onset. Further research is needed to better understand the relationship between COVID-19 vaccinations and PASC.